Monochorionic diamniotic twin pregnancy with selective IUGR type 2: fetoscopic and sonographic findings of ominous prognosis - Gil Guevara, Enrique (2016)
A woman with a monochorionic diamniotic twin pregnancy was referred to our Centre due to a discrepancy in size between the foetuses. She was 17 weeks’ pregnant when the diagnosis of selective IUGR type 2 was made and the laser ablation of the placental anastomoses was performed. During the fetoscopy, we identified an arterio-venous anastomosis with bidirectional flow, which is atypical in this type of anastomoses (unidirectionals) and could represent a sign of ominous prognosis for the restricted twin.